2018
DOI: 10.4103/ejd.ejd_92_17
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of tooth wear on facial and oral surfaces and risk factors in young Nigerian adults

Abstract: Objective:The objective of this study is to assess the prevalence of tooth wear and to identify risk factors in a sample of young Nigerian adults.Materials and Methods:Participants were individuals aged 18–35 years, attending dental clinics located in eight centers representing the six geopolitical zones of the country. Calibrated examiners measured tooth wear using basic erosive wear examination (BEWE) index. Individuals were characterized by the highest BEWE score recorded for any facial/oral tooth surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Medical history was the second most frequently studied factor (67% of included studies; n = 183), 2,3,5,22–24,26–35,38,40,42–44,47,49–51,53,56–58,60–64,68–70,74,75,77,78,80,81,83,85,87,90–92,94–96,98,101,102,104–108,110,111,113,114,119–130,132,136–138,140–144,147,148,151,153–157,159,161,162,166,167,169,172,173,176–178, 180,181,185,188–190,194,196,197,199–256 and 27 studies were exclusively dedicated to this topic. The influence of the presence of GORD, stomach upset or heartburn was the most studied factor from this category, with 35.2% of studies included in this scoping review (96 out of 273).…”
Section: Resultsmentioning
confidence: 99%
“…Medical history was the second most frequently studied factor (67% of included studies; n = 183), 2,3,5,22–24,26–35,38,40,42–44,47,49–51,53,56–58,60–64,68–70,74,75,77,78,80,81,83,85,87,90–92,94–96,98,101,102,104–108,110,111,113,114,119–130,132,136–138,140–144,147,148,151,153–157,159,161,162,166,167,169,172,173,176–178, 180,181,185,188–190,194,196,197,199–256 and 27 studies were exclusively dedicated to this topic. The influence of the presence of GORD, stomach upset or heartburn was the most studied factor from this category, with 35.2% of studies included in this scoping review (96 out of 273).…”
Section: Resultsmentioning
confidence: 99%
“…22 Interestingly, tooth wear was negatively associated with level of education (p = 0.013), which coincides with several other studies. 4,[23][24][25] This is in contrast with one study in the UK, evaluating the impact of tooth wear on patients' quality of life and acceptance of their dentition, where level of education was positively correlated to tooth wear severity (r= 0.252, p=0.02). 4 The negative association with level of education was seen in two studies in Nigeria, one in a rural community and the other a national survey of tooth wear in young adults, suggesting a significant association (p < 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…4 The negative association with level of education was seen in two studies in Nigeria, one in a rural community and the other a national survey of tooth wear in young adults, suggesting a significant association (p < 0.05). 23,24 Overall, education level was reported to be linked to several health outcomes, where rates differed between high and low education levels. 25 Educated individuals tend to consume a healthier diet in addition to practicing better oral hygiene, which would also protect their teeth.…”
Section: Discussionmentioning
confidence: 99%
“…From this group, 40 contained data on participants but were mainly on children or adolescents and only 8 reported data on adults. 7,19,20,[32][33][34][35] From these studies, the highest risk factors were the frequency of acidic foods taken outside meals. Lussi et al, in a number of studies in Switzerland, also identified acidic beverages and food in their studies.…”
Section: Focus Question 2: What Causes Tooth Wear?mentioning
confidence: 99%
“…The remainder of the studies are epidemiological and cross‐sectional studies. From this group, 40 contained data on participants but were mainly on children or adolescents and only 8 reported data on adults 7,19,20,32–35 . From these studies, the highest risk factors were the frequency of acidic foods taken outside meals.…”
Section: Focus Question 2: What Causes Tooth Wear?mentioning
confidence: 99%